PENGARUH SEASONAL EFFECT TERHADAP RETURN SAHAM LQ-45 DI BURSA EFEK INDONESIA TAHUN 2019 – 2020 - Budiman Budiman; Nur aida Arifah Tara; I Nyoman Nugraha AP (Master of Management, Mataram University, 2021)
The purpose of this research was to examine the existence of Monday Effect, Week Four Effect, and Rogalsky Effect on stock return of LQ-45 index ini Indonesian Stock Exchange (IDX) during 2019 – 2020. The statistic methods used to test the hypotheses are Mann Whitney. The results show that Monday Effect, Week Four Effect, and Rogalsky Effect exist on stock return of LQ-45 index in IDX.Keywords :Monday Effect, Week Four Effect, Rogalsky Effect, Return